Analysis of the Impact of Construction and Demolition Waste Project in Surabaya on Socio-Economics and the Environment - Michella Beatrix; Gede Sarya; Nurani Hartatik (Universitas Islam Raden Rahmat, Malang, 2024)
Surabaya is the second largest city in Indonesia, which has a developing construction industry. Many ongoing projects indicate this, be it road construction projects, buildings, warehouses, etc. As more construction work occurs, more construction and demolition waste is generated, which can impact the social, economic, and environmental impacts. This research aims to measure the magnitude of the impact of construction and demolition waste on projects in Surabaya. Measuring the importance of the impact uses respondents' perceptions using an instrument in the form of a questionnaire, where the respondents in this study are contractors working on construction and demolition projects in Surabaya. The collected questionnaires were processed using the Partial Least Square (PLS) method with SmartpLS 4.0 software. The results obtained were that the impact of construction and demolition waste on social factors was 28.5%, economic factors 39.9%, and environmental factors 52.6%.